Multidrug resistance in bacteria associated with leafy greens and soil in urban agriculture systems - Harrelson, Erin; Zeng, Qingyue; Gao, Mairui; Toro, Magaly; Blaustein, Ryan A. (Frontiers in Plant Science, 2025)
Urban farms and community gardens support local food production, though these agroecosystems can contain emerging environmental contaminants that may contribute to the dissemination of antimicrobial resistance (AMR). Our previous research enumerated AMR bacteria associated with leafy vegetable production environments in the greater Washington, D.C. area, identifying >100 isolates with multidrug-resistant (MDR) phenotypes. Here, we performed whole genome sequencing analysis of 87 of these strains recovered from leafy greens (n=29), root zone soil (n=42), and bulk soil (n=16) to comprehensively characterize their MDR genotypes, including taxonomy and any encoded ARGs, stress response genes, and mobile genetic elements (MGEs; e.g., plasmids, phages, conjugative elements). The MDR isolates spanned 4 phyla and 14 genera, with the majority identified as Pseudomonas (n = 29), Serratia (n = 22), Providencia (n = 11), and Bacillus (n = 11). Most of the ARGs were linked to multidrug efflux, while other abundant ARG classes reflected resistance to beta-lactams and tetracyclines. While the genotypes were often conserved within respective species and even genera, the observed phenotypes within taxonomic groups slightly varied, suggesting the potential roles of uncharacterized genetic elements in MDR function. Moreover, all of the MDR isolates encoded at least one gene annotated as a MGE, and there were 19 distinct ARGs located within 5,000 bp upstream or downstream of these sequences, suggesting potential implications for mobilization. Overall, our results indicate that the MDR bacteria in urban agriculture systems, including on fresh produce, are dominated by general soil-associated taxa that carry diverse ARGs and MGEs.